2020
DOI: 10.3390/su12020465
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Service Response to Human Disturbance in the Yangtze River Economic Belt: A Case of Western Hunan, China

Abstract: Ecosystem conservation is one of the core elements of sustainable development. Studying the relationship between human disturbance and the ecosystem service value (ESV) change is an urgent need for the future. The Yangtze River Economic Belt is one of the key economic strategies implemented by the Chinese government and is also a demonstration zone for ecological conservation. Western Hunan is an important ecological barrier in the Yangtze basin where different ethnic groups live together and various cultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The vast river floodplain in this section has been developed into grazing sites and cultivated land for planting corn, wheat, and other field crops [55,56]. Previous results have indicated that frequent human activities, to some extent, adversely affect the wetland plant diversity of the middle and lower reaches of the Yellow River in China [57][58][59].…”
Section: Effects Of Human Disturbance On Plant Diversitymentioning
confidence: 99%
“…The vast river floodplain in this section has been developed into grazing sites and cultivated land for planting corn, wheat, and other field crops [55,56]. Previous results have indicated that frequent human activities, to some extent, adversely affect the wetland plant diversity of the middle and lower reaches of the Yellow River in China [57][58][59].…”
Section: Effects Of Human Disturbance On Plant Diversitymentioning
confidence: 99%
“…NPP is mainly determined by the ecosystem structure, such as the configuration of vegetation [10] and the horizontal and vertical distributions of forests [11]. Many factors such as climate change [12,13], land use transition [14], and human disturbance [15] would change the ecosystem structures, which driving terrestrial NPP dynamics at various spatial scales. Therefore, it is vital to characterize and quantify the spatiotemporal variations of NPP as a result of various driving forces for land use planning and ecosystem regulation.…”
Section: Introductionmentioning
confidence: 99%